EKSPLORASI FAKTOR-FAKTOR KEPUASAN KONSUMEN DI ROUTER COFFEE - Saputra, Oki Galuh (PERFORMA, 2017)
Router Coffee is one of the cafe business in Surabaya that already has enough consumers. Opinions, perceptions, and customer satisfaction have an important role for a company. This study aims to determine what factors are related to consumer satisfaction in Router Coffee by using the factors of service quality, product quality, price, or relationship marketing. The existence of this research is expected to be used as input Router Coffee company to further develop and improve the company through customer satisfaction in accordance with existing theory. Data collection method used by the author in this study is the interview and documentation. The study involved seven respondents, three Router Coffee customers with a one-week visit intensity, two customers with two-week visit intensity, and two new customers who first visited Router Coffee. Data analysis technique in this research is divided into three stages namely, data reduction, data presentation, and drawing conclusion. The result of this research indicate that the factor of service quality, product quality, price, and relationship marketing have related to consumer satisfaction in Router Coffee. This decision is taken by the authors of several things: the results of interviews to selected consumers, the results of internal and external documentation company. By knowing the factors related to consumer satisfaction in Router Coffee expected the company can make these factors as a reference to achieve customer satisfaction, so the company is expected to improve better earnings in the future.